2017
DOI: 10.5430/ijhe.v6n3p82
|View full text |Cite
|
Sign up to set email alerts
|

Development of Critical Thinking Skills through Writing Tasks: Challenges Facing Maritime English Students at Aqaba College, AlBalqa Applied University, Jordan

Abstract: Teaching English for Special Purposes (ESP) in a context where English is taught as a Foreign Language (EFL) is no easy task. There is in fact extensive research reporting on challenges facing both teacher and student in the Foreign Language classroom where language skills must be learnt outside their usual context. Even more challenging is teaching or learning a conceptual skill like critical thinking through writing in an EFL context. The objective of this paper is to identify and describe writing tasks cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
2
10
1
1
Order By: Relevance
“…Results from lessons held over a 15-month period in 2013 and 2014 showed that 14 of the 15 success factors improved, with three of them (intrinsic goal orientation, self-efficacy, and critical thinking) statistically significant. Alidmat and Ayassrah (2017) investigated how critical thinking abilities can be developed in ESP courses using properly selected English writing challenges. In-depth was employed as the instrument in the qualitative investigation.…”
Section: The Combination Of Writing Process and Critical Thinkingmentioning
confidence: 99%
“…Results from lessons held over a 15-month period in 2013 and 2014 showed that 14 of the 15 success factors improved, with three of them (intrinsic goal orientation, self-efficacy, and critical thinking) statistically significant. Alidmat and Ayassrah (2017) investigated how critical thinking abilities can be developed in ESP courses using properly selected English writing challenges. In-depth was employed as the instrument in the qualitative investigation.…”
Section: The Combination Of Writing Process and Critical Thinkingmentioning
confidence: 99%
“…Students have to be simultaneously exposed to four basic skills like listening, speaking, reading, and writing skills in English for specific purpose programs. As to thinking, writing is recognized as a medium of shadowing someone' own understanding (Alidmat & Ayassrah, 2017). The productive feature of writing skill can be challenging if the tasks are not well-defined, because writing means detecting how to find the most influential aspect for transferring information.…”
Section: Writing and Critical Thinkingmentioning
confidence: 99%
“…Unlike face-to-face meetings among the group members to discuss the drafts of the writing, blog or weblog would allow the members to communicate with another faster and more frequent, share their drafts faster, improve their drafts faster and produce their final written products with great satisfaction. Moreover, Alidmat & Ayassrah (2017) indicated that writing tasks like copying or writing down dictated notes did not require cognition of any sort. Higher level writing tasks demanding evaluation, inference, comparison or examination were similarly of no use to the beginning writer who still should learn how to compose ideas.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%